Comparative Structural and Functional Analyses of the Fusiform, Oval, and Triradiate Morphotypes of Phaeodactylum tricornutum Pt3 Strain - Galas, Ludovic; Burel, Carole; Schapman, Damien; Ropitaux, Marc; Bernard, Sophie; Bénard, Magalie; Bardor, Muriel (Frontiers in Plant Science, 2021)
Recently used as a cell biofactory, the diatom Phaeodactylum tricornutum is a marine unicellular microalga that exists under three main morphotypes: oval, fusiform and triradiate. Previous work have demonstrated that the oval morphotype of P. tricornutum Pt3 strain present specific metabolic features. Here, we compared the cellular organization of the main morphotypes of the diatom P. tricornutum Pt3 strain through transmitted electron and advanced light microscopies. The three morphotypes share similarities including spectral characteristics of the chloroplast, the location of the nucleus, the organization of mitochondria around the chloroplast as well as the existence of both a F-actin cortex and an intracellular network of F-actin. In contrast, as compare to fusiform and triradiate cells, oval cells release spontaneously proteins more rapidly. In addition, the down-regulation of a number of genes involved in the polymerization of actin and the overexpression of vesicle trafficking genes in the oval morphotype as compared to the fusiform and triradiate suggest a specific activation of the secretory machinery in oval cells. This study highlights the specificities occurring within the oval morphotype confirming that the oval cells secrete proteins more rapidly. This is of particular interest as P. tricornutum has been used recently to produce recombinant monoclonal antibodies. However, the production yield is insufficient to envision an industrial commercialization. Thus, gaining comprehension of P. tricornutum cellular and metabolism processes would be helpful in the future to maximize the use of P. tricornutum as a green alternative cell biofactory. The results presented in this study suggests that using oval cells for the production of biopharmaceutical proteins might be helpful to improve the production yield. In addition, characterizing the secretory pathways by which proteins such as recombinant mAbs are released would be of particular interest in this blue biotech context.